Womens in the young supporters of Grêmio Football Porto-Alegrense - Silva, Carolina Fernandes (2016)
In Rio Grande do Sul state, Brazil, the participation of women supporters the two biggest football clubs is increasing. There is the significant participation of women in the Young Supporters Organized, founded in 1977, considered the oldest fans organized activity of Grêmio Foot-Ball Porto Alegrense, located in the state capital of Rio Grande do Sul. The aim is to understand how to set up women's participation in the Young Fans of Grêmio Foot-Ball Porto Alegrense. The methodological procedures adopted were searching for documents, on websites, the free observation and semi-structured interview. The hierarchical structure organized this crowd made it possible for the participating women assume symbols and organized supporter ideologies, composing a female nucleus that is present to this day in games of Grêmio Foot-Ball Porto Alegrense.